2015
DOI: 10.1080/17461391.2015.1010106
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying positional and temporal movement patterns in professional rugby union using global positioning system

Abstract: This study assessed the positional and temporal movement patterns of professional rugby union players during competition using global positioning system (GPS) units. GPS data were collected from 33 professional rugby players from 13 matches throughout the 2012-2013 season sampling at 10 Hz. Players wore GPS units from which information on distances, velocities, accelerations, exertion index, player load, contacts, sprinting and repeated high-intensity efforts (RHIE) were derived. Data files from players who pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
131
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(160 citation statements)
references
References 27 publications
24
131
4
1
Order By: Relevance
“…Roberts et al 7 reported no difference in total distance or high intensity running distance between match halves for all players. Jones et al 8 also reported no difference in total, high or low speed distance per half, although there were reductions in cruising (2.7 to 3.8 m.s -1 ) and striding (3.8 to 5.0 m.s -1 ) distance for all players. The large differences the physical requirements of players in different positions has been regularly documented 13,14 , and it is possible that important information was missed in these studies due to the heterogeneity of the player groups.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Roberts et al 7 reported no difference in total distance or high intensity running distance between match halves for all players. Jones et al 8 also reported no difference in total, high or low speed distance per half, although there were reductions in cruising (2.7 to 3.8 m.s -1 ) and striding (3.8 to 5.0 m.s -1 ) distance for all players. The large differences the physical requirements of players in different positions has been regularly documented 13,14 , and it is possible that important information was missed in these studies due to the heterogeneity of the player groups.…”
Section: Discussionmentioning
confidence: 97%
“…Roberts et al 7 reported that high intensity running distance remained consistent throughout match segments. In contrast, Jones et al 8 showed large reductions (~50%) in high intensity running in periods 30-40 minutes and 50-60 minutes during match play. Lacome et al 6 found no change in exercise to rest ratios from 1 st to 2 nd half in international rugby players, concluding that there was not an obvious decrease in performance due to fatigue 6 , indicating a 'flat' pacing strategy.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…The locomotive demands of senior professional players have recently been quantified using global positioning systems (GPS) technology (4,5,30). Cahill et al (4) found that in senior players, backs covered greater total (6545 ± 1055 vs. 5850 ± 1101 m) and relative (71.1 ± 11.7 vs. 64.6 ± 6.3 m.min -1 ) distances than forwards in addition to recording a higher maximum velocity (8.4 ± 0.9 vs. 7.3 ± 1.1 m.s -1 ) during sprinting.…”
Section: Introductionmentioning
confidence: 99%